Biogeographical transition zones: a search for conceptual synthesis. (25th July 2014) - Ferro, Ignacio; Morrone, Juan J.
<x xml:space="preserve">Abstract</x> We revise concepts, definitions and examples of biogeographical transition zones to help develop a conceptual framework and differentiate them from other transitions that occur in the geographical space. A biogeographical transition zone is defined as a geographical area of overlap, with a gradient of replacement and partial segregation between biotic components (sets of taxa that share a similar geographical distribution as a product of a common history). It is an area where physical features, environmental conditions and ecological factors allow the mixture and the co‐occurrence of two or more biotic components, but also constrain their distribution further into one another. The biogeographical affinities of the taxa are the most fundamental information to consider to analyse biogeographical transition zones accurately. By plotting the frequency of different distribution patterns on maps, gradual changes in their relative contribution to a given area can be perceived. Thus, the most heterogeneous places in terms of distributional patterns can be defined numerically on strictly geographical grounds. Biogeographical transition zones can occur at every hierarchical level of a biogeographical regionalization as long as different biotic components come into contact geographically. Ecological boundaries or ecotones when characterized only by differences in dominance of some species, life forms or sets of characteristic species (not endemic) are not biogeographical transition zones as defined herein. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 113, 1–12.